Plumages and primary moult in Lesser Flamingos - Sileo, L; Tuite, C H; Hopcraft, J B D (Wildfowl, 1977)
The relative age of 47 Lesser Flamingos Phoeniconaias minor captured at Lake Nakuru, Kenya, were assessed by two methods: firstly, by external colouration and secondly by bursal condition and thymal atrophy. It appeared that one or both of these parameters is not correlated with chronological age. Examination of the primary moult of a total of 108 birds showed that under some circumstances this species undergoes a partial sequential primary moult rather than the complete simultaneous moult reported previously. It is suggested that such a dual moulting pattern is an adaptation to life in a relatively unpredictable unseasonal tropical environment.